1995
DOI: 10.2166/wst.1995.0036
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of rainfall induced infiltration into separate sewerage

Abstract: Flowrate changes in separate wastewater sewerage during wet weather are often attributed to inappropriate connections of runoff water. But these inputs are not the only cause of such behaviour and infiltration through leaking defects or cracks can supply large flows into collection pipes. The characterization of these flows is not an easy task since they involve complex processes, depending not only on rainfall events but also on hydrological conditions and seasons. Using 16 months of hourly measurements of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Urbanization can change catchment hydrology and morphology rapidly, accelerating gully erosion and causing serious damage to urban structures such as roads, bridges and property (Wolman, 1967;Bryan and Price, 1980;Croke and Mockler, 2001). Urban surface runoff typically exhibits rapid and intense increases during storm events due to water fl owing over impervious surfaces (Belhadj et al, 1995;Berthier et al, 1999;Becciu and Paoletti, 2000;Berthier et al, 2004;Rodriguez et al, 2003). Hence, the establishment of an urban drainage system generally increases the volume and velocity of water discharged into gully headcuts, leading to gully expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Urbanization can change catchment hydrology and morphology rapidly, accelerating gully erosion and causing serious damage to urban structures such as roads, bridges and property (Wolman, 1967;Bryan and Price, 1980;Croke and Mockler, 2001). Urban surface runoff typically exhibits rapid and intense increases during storm events due to water fl owing over impervious surfaces (Belhadj et al, 1995;Berthier et al, 1999;Becciu and Paoletti, 2000;Berthier et al, 2004;Rodriguez et al, 2003). Hence, the establishment of an urban drainage system generally increases the volume and velocity of water discharged into gully headcuts, leading to gully expansion.…”
Section: Introductionmentioning
confidence: 99%
“…The main contribution to the flow rate encompasses the runoff on streets (7.5%) and the runoff on houses (15.1%) but the direct infiltration into sewers represents more than 10% of the total rainfall. These fluxes are not really validated because of the lack of appropriate data, but are in correspondence with experimental results (Hollis and Ovenden, 1988;Belhadj et al, 1995).…”
Section: Simulation Of Runoff Flowsmentioning
confidence: 93%
“…The impervious surface connected to the drainage network is 37% and the soil is considered as a silty clay. This catchment has been continuously monitored since 10 years and has already been used for hydrological modelling tests (Rodriguez et al, 2000;Rodriguez et al, 2003) The data measured encompasses : (i) the rainfall intensity and the discharge at the outlet from 1991 up to 2002; (ii) the daily water table level through three piezometers installed at two locations of the catchment, from September 1995 up to December 1998; (iii) groundwater drainage runoff, measured during three winter periods in wastewater drainage network (Belhadj et al, 1995), and provides a good estimation of both rain-and waste-water drainage (Berthier, 1999); (iv) meteorological data such as Penman evapotranspiration, collected from the meteorological station located 5 km from Rezé. Figure 3a regroups the different measurements and shows the catchment morphology.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Various experiments and observations (Belhadj et al, 1995;Lerner, 2002;Berthier et al, 2004;Le Delliou et al, 2009) have shown that soil water drainage occurs when artificial networks are situated under saturated soil moisture conditions. 15…”
Section: Drainage Of Soil Water By the Sewer Networkmentioning
confidence: 99%